Characterization of the N-terminal domain of BteA: a Bordetella type III secreted cytotoxic effector. - Chen Guttman; Geula Davidov; Hadassa Shaked; Sofiya Kolusheva; Ronit Bitton; Atish Ganguly; Jeff F Miller; Jordan H Chill; Raz Zarivach (PLoS ONE, 2013)
BteA, a 69-kDa cytotoxic protein, is a type III secretion system (T3SS) effector in the classical Bordetella, the etiological agents of pertussis and related mammalian respiratory diseases. Currently there is limited information regarding the structure of BteA or its subdomains, and no insight as to the identity of its eukaryotic partners(s) and their modes of interaction with BteA. The mechanisms that lead to BteA dependent cell death also remain elusive. The N-terminal domain of BteA is multifunctional, acting as a docking platform for its cognate chaperone (BtcA) in the bacterium, and targeting the protein to lipid raft microdomains within the eukaryotic host cell. In this study we describe the biochemical and biophysical characteristics of this domain (BteA287) and determine its architecture. We characterize BteA287 as being a soluble and highly stable domain which is rich in alpha helical content. Nuclear magnetic resonance (NMR) experiments combined with size exclusion and analytical ultracentrifugation measurements confirm these observations and reveal BteA287 to be monomeric in nature with a tendency to oligomerize at concentrations above 200 µM. Furthermore, diffusion-NMR demonstrated that the first 31 residues of BteA287 are responsible for the apparent aggregation behavior of BteA287. Light scattering analyses and small angle X-ray scattering experiments reveal a prolate ellipsoidal bi-pyramidal dumb-bell shape. Thus, our biophysical characterization is a first step towards structure determination of the BteA N-terminal domain.